Evidence for Cross-species Influenza A Virus Transmission Within Swine Farms, China: A One Health, Prospective Cohort Study. (16th September 2017) - Ma, Mai-Juan; Wang, Guo-Lin; Anderson, Benjamin D; Bi, Zhen-Qiang; Lu, Bing; Wang, Xian-Jun; Wang, Chuang-Xin; Chen, Shan-Hui; Qian, Yan-Hua; Song, Shao-Xia; Li, Min; Lednicky, John A; et al.
Abstract : In a comprehensive, 12-month study of 6 swine farms in China, we found considerable evidence of multiple influenza A viruses likely reassorting and likely crossing species within the farms. Increased surveillance for novel influenza virus emergence on swine farms is greatly needed. Abstract: Background: Our understanding of influenza A virus transmission between humans and pigs is limited. Methods: Beginning in 2015, we used a One Health approach and serial sampling to prospectively study 299 swine workers and 100 controls, their 9000 pigs, and 6 pig farm environments in China for influenza A viruses (IAVs) using molecular, culture, and immunological techniques. Study participants were closely monitored for influenza-like illness (ILI) events. Results: Upon enrollment, swine workers had higher serum neutralizing antibody titers against swine H1N1 and higher nasal wash total immunoglobulin A (IgA) and specific IgA titers against swine H1N1 and H3N2 viruses. Over a period of 12 months, IAVs were detected by quantitative reverse-transcription polymerase chain reaction in 46 of 396 (11.6%) environmental swabs, 235 of 3300 (7.1%) pig oral secretion, 23 of 396 (5.8%) water, 20 of 396 (5.1%) aerosol, and 19 of 396 (4.8%) fecal-slurry specimens. Five of 32 (15.6%) participants with ILI events had nasopharyngeal swab specimens that were positive for IAV, and 17 (53.1%) demonstrated 4-fold rises in neutralization titers against a swine virus. Reassorted Eurasian avian-lineage H1N1, A(H1N1)pdm09-like, and swine-lineage H3N2 viruses were identified in pig farms. The A(H1N1)pdm09-like H1N1 viruses identified in swine were nearly genetically identical to the human H1N1 viruses isolated from the participants with ILI. Conclusions: There was considerable evidence of A(H1N1)pdm09-like, swine-lineage H1N1, and swine-lineage H3N2 viruses circulating, likely reassorting, and likely crossing species within the pig farms. These data suggest that stronger surveillance for novel influenza virus emergence within swine farms is imperative.